A humanized yeast proteasome identifies unique binding modes of inhibitors for the immunosubunit β5i. (27th October 2016) - Huber, Eva M; Heinemeyer, Wolfgang; de Bruin, Gerjan; Overkleeft, Herman S; Groll, Michael
Abstract: Inhibition of the immunoproteasome subunit β5i alleviates autoimmune diseases in preclinical studies and represents a promising new anti‐inflammatory therapy. However, the lack of structural data on the human immunoproteasome still hampers drug design. Here, we systematically determined the potency of seven α' β' epoxyketone inhibitors with varying N‐caps and P3‐stereochemistry for mouse/human β5c/β5i and found pronounced differences in their subunit and species selectivity. Using X‐ray crystallography, the compounds were analyzed for their modes of binding to chimeric yeast proteasomes that incorporate key parts of human β5c, human β5i or mouse β5i and the neighboring β6 subunit. The structural data reveal exceptional conformations for the most selective human β5i inhibitors and highlight subtle structural differences as the major reason for the observed species selectivity. Altogether, the presented results validate the humanized yeast proteasome as a powerful tool for structure‐based development of β5i inhibitors with potential clinical applications. Synopsis: Inhibitors of the immunoproteasome are potential anti‐inflammatory drugs. Crystallographic data on yeast/mammalian chimeric proteasomes uncover distinct binding modes of ligands with non‐natural stereochemistry and provide explanation for the enhanced species and subunit selectivities towards human β5i that have been observed in inhibition assays. Chimeric proteasomes were created by replacing key parts of the yeast β5 and β6 subunits with the mammalian counterparts. Structural equivalence of the β5i chimeric proteasomes to the genuine mouse iCP structure was proven by X‐ray crystallography. Distinct binding modes of PR‐924 and related inhibitors to β5c and β5i chimeric proteasomes provide explanation for their enhanced β5i selectivity. PR‐924 and its derivatives target human β5i over mouse β5i, as the mouse‐specific β5i residue Met31 hinders their binding to the murine immunosubunit. Abstract : Engineering of chimeric yeast/mammalian proteasomes allows crystallographic elucidation of the binding modes and specificities of immunoproteasome inhibitors, which are promising anti‐inflammatory drug candidates.